2014
DOI: 10.1037/xlm0000006
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting as a consequence and enabler of creative thinking.

Abstract: Four experiments examined the interplay of memory and creative cognition, showing that attempting to think of new uses for an object can cause the forgetting of old uses. Specifically, using an adapted version of the Alternative Uses Task (Guilford, 1957), participants studied several uses for a variety of common household objects before attempting to generate new uses for half of those objects. As revealed by performance on a final cued-recall task, attempting to generate new uses caused participants to forge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 142 publications
(226 reference statements)
8
43
0
Order By: Relevance
“…The specificity induction also produced very similar effects as observed in our previous studies (Madore et al, 2014; Madore & Schacter, 2014, 2015) on an imagination task, boosting the number of episodic but not semantic details that participants generated when they imagined possible future events. The parallel effects of the specificity induction on divergent thinking and imagination provide novel support for the idea that both draw importantly on episodic retrieval, consistent with previous findings and ideas about creative cognition (Addis et al, 2014; Benedek et al, 2014; Ellamil et al, 2012; Finke, Ward, & Smith, 1992; Gilhooly et al, 2007; Smith, 1995; Smith & Ward, 2012), and to our knowledge the first evidence that an experimental manipulation that specifically increases episodic retrieval also increases a measure of creative thinking (for an example of related evidence, see Storm & Patel, 2014). …”
Section: Experiments 1 Discussionsupporting
confidence: 85%
“…The specificity induction also produced very similar effects as observed in our previous studies (Madore et al, 2014; Madore & Schacter, 2014, 2015) on an imagination task, boosting the number of episodic but not semantic details that participants generated when they imagined possible future events. The parallel effects of the specificity induction on divergent thinking and imagination provide novel support for the idea that both draw importantly on episodic retrieval, consistent with previous findings and ideas about creative cognition (Addis et al, 2014; Benedek et al, 2014; Ellamil et al, 2012; Finke, Ward, & Smith, 1992; Gilhooly et al, 2007; Smith, 1995; Smith & Ward, 2012), and to our knowledge the first evidence that an experimental manipulation that specifically increases episodic retrieval also increases a measure of creative thinking (for an example of related evidence, see Storm & Patel, 2014). …”
Section: Experiments 1 Discussionsupporting
confidence: 85%
“…This finding fits well with previous work on retrieval-induced forgetting and fan interference, which has shown that the selective strengthening of some informationwhether through retrieval practice, generation, or some other process-does not result in the impaired accessibility of other information when the two subsets are integrated or highly related (Anderson & McCulloch, 1999;Chan et al, 2006;Radvansky, 1999;Storm & Patel, 2014). In the present context, this finding suggests that the way in which people go about attempting to generate new arguments in support of a position can determine the mnemonic consequences of such attempts.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, effects similar to retrieval-induced forgetting have been observed in almost any situation in which someone must attempt to retrieve or generate some specific subset of information while not retrieving or generating other information (e.g., Bäuml, 2002;Johnson & Anderson, 2004;Healey, Campbell, Hasher, & Ossher, 2010;Levy, McVeigh, Marful, & Anderson, 2007;Storm, Angello, & Bjork, 2011;Storm, Bjork, Bjork, & Nestojko, 2006;Storm & Patel, 2014).…”
Section: Retrieval-induced Forgettingmentioning
confidence: 99%
See 2 more Smart Citations